2020
DOI: 10.1103/physrevlett.124.183201
|View full text |Cite
|
Sign up to set email alerts
|

Driven Imposters: Controlling Expectations in Many-Body Systems

Abstract: We present a framework for controlling the observables of a general correlated electron system driven by an incident laser field. The approach provides a prescription for the driving required to generate an arbitrary predetermined evolution for the expectation value of a chosen observable, together with a constraint on the maximum size of this expectation. To demonstrate this, we determine the laser fields required to exactly control the current in a Fermi-Hubbard system under a range of model parameters, full… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…An analogous physical property is present in HHG systems (see Fig. 1), where it has been shown [36][37][38] that regardless of the physical specifics of the system, there always exists an incident laser field (input) that will induce a desired optical response (output). For this reason, a single atom undergoing HHG provides an appealing platform for computation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…An analogous physical property is present in HHG systems (see Fig. 1), where it has been shown [36][37][38] that regardless of the physical specifics of the system, there always exists an incident laser field (input) that will induce a desired optical response (output). For this reason, a single atom undergoing HHG provides an appealing platform for computation.…”
Section: Introductionmentioning
confidence: 86%
“…HHG occurs when a short and intense laser pulse generates responses of up to ≈ 100 times the frequency of the incident field. It has been shown that both atomic [36] and solid-state [37,38] systems exhibiting HHG also possess the equally desirable property of universality. In a computational context, universality implies that regardless of architecture, any output result can be obtained by suitable input data and software.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interplay of these temporal non-linear strongfield effects with non-perturbative strong electronic correlations, fundamentally changes the optical response of a material and enters a rich emergent regime of novel collective phenomena. This offers the possibility of emission of even higher harmonics due to coupling with these many-body interactions, and the proposal of engineering of photo-induced correlated phases [19][20][21][22]. However, HHG and driving fields in strongly correlated materials is far from understood, and is emerging as a key research challenge in computational non-equilibrium science.…”
Section: Introductionmentioning
confidence: 99%
“…Using tracking quantum control [14][15][16][17][18][19][20][21], recent work has demonstrated that almost arbitrary control over the optical response of a large class of solid-state systems can be achieved [22,23]. One consequence of this is that two specially tailored driving fields will induce an identical response from two distinct systems.…”
mentioning
confidence: 99%
“…Consider a typical example of an optically driven current. The current operator Ĵ(k) is defined from a continuity equation for the electron density [22,23]. Provided all number operators njσ = ĉ † jσ ĉjσ commute with Û (k) , each system's current operator has the form [45]:…”
mentioning
confidence: 99%